Development of Guidance and Counseling Modules to Improve Students' Further Education Planning - Fadhlullah, Zulfikar; Firman, Firman; Netrawati, Netrawati (Universitas Trunojoyo Madura, 2023)
This paper aims to explain the development of guidance and counseling modules to improve student continuing education planning. In 2021 there will still be 87% of Indonesian students making the wrong choice of major. This can have a negative impact on students during the lecture process and can even end in dropping out. And in the future can increase the number of unemployed. The method used in this paper is library research (Library Research). Through this research, it can be concluded that the development of guidance and counseling modules can be a source of information for students in improving students' further education plans so that there are no mistakes in choosing majors in tertiary institutions later.